Pollen specificity elements reside in 30 bp of the proximal promoters of two pollen-expressed genes. - Eyal, Y (1995)
Functional analyses previously identified minimal promoter regions required for maintaining high-level expression of the late anther tomato LAT52 and LAT59 genes in tomato pollen. Here, we now define elements that direct pollen specificity. We used a transient assay system consisting of two cell types that differentially express the LAT genes and both "loss-of-function" and "gain-of-function" approaches. Linker substitution mutants analyzed in the transient assay and in transgenic plants identified 30-bp proximal promoter regions of LAT52 and LAT59 that are essential for their expression in pollen and that confer pollen specificity when fused to the heterologous cauliflower mosaic virus 35S core promoter. In vivo competition experiments demonstrated that a common trans-acting factor interacts with the pollen specificity region of both LAT gene promoters and suggested that a common mechanism regulates their coordinate expression. Adjacent upstream elements, the 52/56 box in LAT52 and the 56/59 box in LAT59, are involved in modulating the level of expression in pollen. The 52/56 box may be a target for the binding of a member of the GT-1 transcription factor family.